2001
DOI: 10.1002/cne.1319
|View full text |Cite
|
Sign up to set email alerts
|

Localization of rat glycine receptor α1 and α2 subunit transcripts in the developing auditory brainstem

Abstract: Glycine receptors (GlyRs), aside from GABA(A) receptors, mediate fast postsynaptic inhibition in the mammalian nervous system. Spatial and temporal expression of the genes encoding ligand-binding alpha subunits (alpha1-alpha4) and the structural beta subunit leads to the formation of various GlyR isoforms. Currently, the idea of the GlyRs containing the "adult" alpha1 subunit replacing those with the "neonatal" alpha2 subunit during early postnatal development predominates. Here, we describe the patterns of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…The trend is not always true in all neural circuits (Lynch, 2009). Our study suggests that such a switch might occur in T-stellate cells during development and might not occur in bushy cells, which would be consistent with the continued presence of α 2 mRNA in the AVCN through adulthood (Piechotta et al, 2001). …”
Section: Discussionsupporting
confidence: 79%
“…The trend is not always true in all neural circuits (Lynch, 2009). Our study suggests that such a switch might occur in T-stellate cells during development and might not occur in bushy cells, which would be consistent with the continued presence of α 2 mRNA in the AVCN through adulthood (Piechotta et al, 2001). …”
Section: Discussionsupporting
confidence: 79%
“…The ␤ subunit is not necessary for forming a functional channel . In the DCN, mRNA studies have shown the presence of the ␣2 subunit only early during development (Sato et al, 2000;Piechotta et al, 2001) and ␣1, ␣3, and ␤ in the adult rat (Sato et al, 2000;Piechotta et al, 2001). At the protein level, the existence of the glycinergic input was previously analyzed by using an antibody against the glycine receptorassociated protein, gephyrin, as an indicator of GlyRs in the cochlear nucleus.…”
Section: Glycine Receptor ␣1 Subunit Is a Key Receptor Subunit Mediatmentioning
confidence: 99%
“…The resulting proteins differ in only two amino acid residues in the extracellular N-terminal part of the receptor (Kuhse et al, 1991). Recent findings suggest that the α2 expression persists into adulthood in retina, cerebellum, and auditory brain stem (Piechotta et al, 2001; Young and Cepko, 2004; Heinze et al, 2007; Nobles et al, 2012). GlyR3α also exists in two splice variants, differing in a 15 amino acid insertion in the TM3-4 loop (α3L and α3K).…”
Section: Glyr Subunit Diversity and Developmental Regulationmentioning
confidence: 99%